Analysis of the load-bearing system of the loader according to the results of dynamic tests in the environment of Ansys motion - Shcherbak, Oleh; Ragulin, Vitaliy; Suminov, Andrii; Щербак, Олег Віталійович; Рагулін, Віталій Миколайович; Сумінов, Андрій Володимирович (Харківський національний автомобільно-дорожній університет, 2022)
Problem. The T-156B hinge frame of the loader, which is an upgraded frame of an agricultural tractor, creates loads during work operations for which it was not designed. Such loads lead to breakdowns and further shorten the life of the entire machine. The frame is the basic element around which the machine is built. The loader that had just been removed from the conveyor did not have builtin durability and reliability. While designing a road construction machine, an account of the features, nature, and conditions of its operation should be taken. Goal. The goal is to develop a hinge frame design technique that takes into account the loads experienced by the frame with a virtual simulation of real-world situations during the loader process. Methodology. The adopted approach is based on the use of a Solidworks computer program with three-dimensional modeling and an Ansys motion program for calculating the dynamics of multicomponent bodies taking into account the hinge and contact interaction. Results. In the work three cases of technological operations of the loader were considered. 1. Lifting a full bucket. 2. Collision with an obstacle that is difficult to overcome 3. Movement over an uneven surface with the raised loader arm. The results of the calculations provided forces and torques in the hinge of the half-frames, as well as the effort of the frame. Based on the results obtained, the endurance of the frame in the Ansys motion software package was calculated. Originality. The analysis of load-bearing systems with a virtual simulation of the machine’s actual behavior with the help of Ansys motion software allows to obtain more accurate results, significantly reducing the time for the design and cost of field testing. Practical value. This approach to the analysis of the carrier system behavior can be recommended for designing and determining the technological capabilities of wheeled, tracked, and special machines.
Аналіз несучої системи навантажувача за результатами динамічних випробувань у середовищі Ansys motion
Keywords: load-bearing system; strength; durability; 3D simulation; dynamics; Solidworks; Ansys Motion; несуча система; міцність; довговічність; тривимірне моделювання; динаміка; Solidworks; Ansys Motion; 621.863; 10.30977/AT.2219-8342.2022.51.0.06